Pengaruh Human Relation dan Motivasi Kerja Terhadap Kinerja Karyawan Toko Bakpia di Kota Yogyakarta - Zulia Retno Astuty; Sabaruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of human relations and work motivation on the performance of employees at bakpia stores in Yogyakarta. The sampling method used was simple random sampling, with a total sample of 75 employees. Primary data collection was conducted through the distribution of questionnaires that had been tested for validity and reliability. The analysis in this study employed multiple linear regression analysis using IBM SPSS 26. The instrument test results indicated that the data were valid and reliable. The t-test results for the human relations variable showed a t-value of 8.921 > t-table value of 1.666 and a beta coefficient of 0.661, with a significance value of 0.000 < 0.05, indicating a positive and significant influence on employee performance. Similarly, the t-test results for the work motivation variable showed a t-value of 4.065 > t-table value of 1.666 and a beta coefficient of 0.301, with a significance value of 0.000 < 0.05, meaning that work motivation also has a positive and significant influence on employee performance. The F-test results showed that human relations and work motivation simultaneously have a significant effect on employee performance, with an F-value of 164.832 > F-table value of 3.12 and a significance value of 0.000 < 0.05. Based on the coefficient of determination, the Adjusted R Square value was 0.816, meaning that 81.6% of the variations in employee performance are explained by human relations and work motivation variables, while the remaining 18.4% is influenced by other variables not included in this research model.